Cumulative exergetic assessment of LPFO utilised steam boilers. (14th September 2012) - Ohijeagbon, I.O.; Jekayinfa, S.O.; Waheed, M.A.
This paper relates to a study on the energy and exergy resources, transfers, consumption and losses in the combustion and heat exchanging units of industrial steam boilers. Mass, energy and exergy analyses, which included the physical and chemical exergies of material streams, were used to investigate the energy resource utilisation of Low Pour Fuel Oil (LPFO) in industrial steam boilers. The chemical exergies of LPFO and the exhaust flue gases were determined as 44, 566.66 and 147.97 kJ/kg, respectively, for LPFO undergoing complete combustion process. Higher evaporation ratios and energy consumption by steam were associated with reduction in heat loss. Lower exergy destruction was due to lower rapid changes in temperature potential for the generation of steam in the heat exchanging unit. The average energy and exergy efficiencies of the boilers are obtained as 69.54 and 38.5%, respectively. The exergy efficiencies obtained for the combustion and heat exchanging units for the boilers investigated are given as 55.35, 49.06 and 58.69 and 63.80%, respectively. The results obtained in this study could be applied for energy resources management and control of oil–fired industrial steam boilers.